Early Islamic law in Basra in the 2nd/8th century : Aqwāl Qatāda born Diʻāma al-Sadūsī - Al-Salimi, Abdulrahman. (Islamic History and Civilization, 2018)
The manuscript of the Aqwāl Qatāda has repeatedly attracted particular interest among modern scholars, as it raises questions concerning the early development of the Ibāḍī Basran community and the emergence of Islamic jurisprudence in Iraq. It is a unique document because it attests to the existence of a scholarly link between Sunnīs and Ibāḍīs during the early development of Islamic law. The fact that the legal responsa and traditions of Qatāda born Diʿāma al-Sadūsī (60/680-117/735) are part of an Ibāḍī collection, in which the traditions of Ibāḍī Imam Jābir born Zayd (d. 93/ 711) have been transmitted through ʿAmr born Harim and ʿAmr born Dīnār, proves that the Ibāḍī lawyers of the first generations considered Qatāda to be a faithful upholder of Jābir's doctrine. Given the lack of material available for Jābir , instructions must have been given to collect whatever was transmitted through Qatāda. Qatāda's legal responsa must have corresponded to those of the first Ibāḍī authorities, which explains why the collator of the Aqwāl Qatāda (probably Abū Ghānim al-Khurāsānī) included them in an Ibāḍī manuscript. The present volume sheds light on the relationship between the Aqwāl Qatāda and Ibāḍī authorities such as al-Rabī, Abū Ubayda, and Jābir.